Keberhasilan Program Tahfidz Al-Qur'an Kejar Paket B Darul Qur'an Al-Karim Baturaden Banyumas T.A. 2018-2019 - Aziz, Safrudin (TADRIS: Jurnal Pendidikan Islam, 2019)
The study entitled The Success of the Tahfidz al-Qur'an Program on the Pursuit of Package B Daqu al-Karim Banyumas Baturraden is motivated by several things including: First, Tahfidz 30 juz program of the Pursuit of Package B Daqu al-Karim is the only flagship program in Banyumas Regency. Second, the success rate of the Tahfidz program reaches 82%. Thirdly, Daqu al-Karim's Tahfidz Package B program has an applicative curriculum that is arranged in a planned, measurable manner and takes into account the environment, culture, and conditions of the child. Data collection in this study using the method of observation, interviews and documentation. The data analysis is done through the process of data reduction, data display and drawing conclusions and verification.The results of this study indicate the success of the Tahfidz al-Qur'an program on the Pursuit of Package B Daqu al-Karim in the 2018-2019 school year was determined by the institution's vision policy and strengthening strategies implemented in the program: first, prepare the tahfidz curriculum applicatively. Second, tighten the selection of recruitment of teaching staff and prospective students. Third, strengthen the development of learning methods. Fourth, improve leadership quality. Fifth, create cooperation and agreement to approve the program. As well as the sixth, implementing program evaluation and control. The six strategies are synergized with each other and the implementation is evaluated based on the target targets that have been determined. Keywords: Tahfidz al-Qur'an, Pursue Package B, Non Formal Education.